Spatial and Temporal Variability of Bed Exchange Characteristics of Fine Sediments From the Weser Estuary - Patzke, J.; Nehlsen, E.; Fröhle, P.; Hesse, R. F. (Frontiers in Earth Science, 2022)
Sedimentation of fine-grained sediments in estuaries is a natural physical phenomenon influenced by biogeochemical processes. In the estuarine turbidity maximum (ETM), enhanced net deposition of sediments is observed even in areas with higher hydrodynamic exposure, such as the navigational channel. Maintenance dredging is a common method to maintain the navigational channel, which requires large financial effort and has potential negative impacts on the environment. Research at the Institute for River and Coastal Engineering addresses the challenge of understanding the processes leading to net sedimentation and accumulation in estuarine navigational channels in reach of the ETM. In this contribution, investigations of bed exchange properties of estuarine cohesive sediments conducted in field and laboratory studies are presented. The results provide rarely available and estuary-specific parameters characterizing sediment transport, mainly related to erosion processes. By performing field campaigns within the ETM of the Weser estuary, cores of freshly deposited sediments have been sampled from two sites (Blexer Bogen and Nordenham) along the center of the navigational channel. Sediment characteristics (grain size distribution, water content, loss on ignition, density profiles) have been derived, and the erodibility of the deposits is investigated both quasi in situ and in the laboratory using an erosion microcosm system. Erodibility experiments are run in a closed system so sediment concentration above the lutocline increases during the experiment. This is a unique feature of this study, and it is expected to produce more natural characteristics of net erosion. By proving the reproducibility of the natural structure of the deposited sediments (stratification and density profiles) in the laboratory, systematic studies for analyzing the sensitivity of determined parameters (shear stresses and erosion rates) to varying environmental conditions (settling conditions and density) could be performed. Temporal development of suspended sediment concentration and erosion rates is the main result of the erodibility experiments, from which we derive bandwidths for erosion parameters, like floc erosion rate, critical shear for floc erosion, and critical shear for mass erosion.